Silane Modification of Crumb Rubber on the Rheological Properties of Rubberized Asphalt - Yunbao Zhang; Zhaohui Liu; Juan Peng (Applied Sciences, 2019)
Because there is a lack of studies on rubberized asphalt based on silane coupling agent modification, KH-550 modified crumb rubber and rubberized asphalts incorporating normal rubber and modified rubber were prepared, respectively. The rheological properties of asphalt samples were evaluated by a dynamic shearing rheometer and a bending beam rheometer; then, mechanisms of KH-550 on rubber surface and functional group changes were analyzed by a Brunauer−Emmett−Teller specific surface area measurement and a Fourier transform infrared spectroscopy. The results imply that: (i) rubber surface area rises and chemical reactions accrue between rubber and asphalt; (ii) modified rubber achieves a more stable state within asphalt, which helps to enhance the mechanical properties of asphalt; (iii) modified rubber helps asphalt to dissipate stress so as to resist the formation of cracks and deformation under low temperature conditions.